Effect of distributed generation placement on power system: A case study of Eko electricity distribution company, LAGOS. Issue 1 (January 2021) - Bango Owolabi, P.; Agbetuyi, A. F.; Samuel, I. A.; Abdulkareem, A.; Adoghe, A. U
Abstract: Protection coordination of distribution network has been one of the issues with the distributed generators integration. The reason is that the distribution network is radial in nature by which energy flow is unidirectional. The research aim is to investigate how the location or placement of DG affects the protection setting of the existing network. The healthiness of the test distribution system used in this work is investigated with and without DG connection by use of load flow analysis using Neplan software. The results confirm that the location or placement of DG with the distribution system connection improves the voltage profiles at each bus and active power load loss. The DG placed 1km away from point of common coupling (PCC), the voltage profiles is 10.448Kv with DG connection, and 10.442kV without DG connection, while active power load loss is 69kW with DG connection and 71kW without DG connection. Also, DG placed 6km away from point of common coupling the voltage profiles is 10. 404kV with DG connection 10.372Kv without DG connection, while the active power load loss is 110kW with DG connection and 131kW without DG is connected. Moreover, with the DG placed 1km away from the point of common coupling (PCC) the fault current 17.596kA with DG connection and 3.286kA without DG connection, while 6km away from the PCC is 17.543kA with DG connection and 3.286kA without DG connection. It can be concluded that as the distance of the DG from the PCC increases, the fault current also increases which affects the protection scheme of the existing distribution system.